Identification of the optimal hsTnI cut-off value for risk stratification of normotensive patients with pulmonary embolism. (25th November 2020) - Ebner, M; Guddat, N; Keller, K; Merten, M.C; Lerchbaumer, M.H; Hasenfuss, G; Konstantinides, S.V; Lankeit, M
Abstract: Background/Introduction: While numerous studies confirmed the prognostic role of high-sensitivity troponin T (hsTnT) in pulmonary embolism (PE), the prognostic relevance of high-sensitivity troponin I (hsTnI) is inappropriately studied and disease specific cut-off values remain undefined. Purpose: To investigate the prognostic relevance of hsTnI in normotensive PE patients, establish the optimal cut-off value for risk stratification and compare the prognostic performances of hsTnI and hsTnT. Methods: Consecutive PE patients enrolled in a prospective single-centre registry between 09/2008 and 04/2018 were studied. Using receiver operating curve analysis, an optimised hsTnI cut-off concentration was identified and the prognostic value for the prediction of in-hospital adverse outcomes (PE-related death, cardiopulmonary resuscitation or vasopressor treatment) and all-cause mortality analysed. Results: We analysed data from 459 PE patients (age 69 [interquartile range (IQR) 57–77] years, 52% female). Patients who suffered an in-hospital adverse outcome (4.8%) had higher median hsTnI concentrations compared to those with a favorable clinical course (57 [IQR 22–197] vs. 15 [IQR 10–86] pg/ml, p=0.03). A hsTnI cut-off value of 16 ng/ml provided the best prognostic performance and predicted an in-hospital adverse outcome (Odds ratio [OR] 6.5, 95% confidence interval [CI] 1.9–22.4) and all-cause mortality (OR 3.7, 95% CI 1.0–13.3). Between female and male patients, no relevant differences in hsTnI concentrations (17 [IQR 10–97] vs. 17 [IQR 10–92] pg/ml, p=0.79) or optimized cut-off values (17 pg/ml and 19 pg/ml, respectively) were observed. Stratification of patients to risk classes according to the 2019 European Society of Cardiology (ESC) algorithm revealed no differences if calculated based on either hsTnI or hsTnT (Table). Conclusions: Our findings confirm the prognostic relevance of hsTnI in normotensive PE. An optimal hsTnI cut-off value of 16 pg/ml predicted in-hospital adverse outcome and all-cause mortality. The use of sex specific cut-off values does not appear necessary. Importantly, our results suggest that hsTnI and hsTnT can be used interchangeably for risk stratification. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): This study was supported by the German Federal Ministry of Education and Research (BMBF 01EO1503). BRAHMS GmbH, part of Thermo Fisher Scientific, Hennigsdorf/Berlin, Germany provided financial support for biomarker measurements. The sponsor was neither involved in biomarker measurements, statistical analyses, writing of the abstract nor had any influence on the scientific contents.